Penelitian Public Relation Eiger Adventure - Seta, Rio Aria (LPPM Universitas Bina Sarana Informatika, 2022)
Public relations (PR) has an important role both for institutions and for the external public. PR plays a role in providing accurate, precise information so that it can be accepted and understood by the public. When the information received by the public can be understood, of course, the assumption of ignorance of an institution can turn into an understanding of what the institution has done and is able to provide a positive image. The research method used is descriptive qualitative observation, namely analyzing the content of Instagram posts and Twitter Eiger and the contents of netizen comments. Research instruments are tools that are needed or used to collect data. This study was analyzed based on the theory of image recovery. The results of this study indicate that the Eiger party implements an image restoration strategy through social media in order to change public perceptions and attitudes, namely quickly and accurately responding to apologies through the content of